Math and Arithmetic
Algebra
Calculus

What is x squared plus 12x plus 36 equals?

012

Top Answer
User Avatar
Wiki User
Answered
2013-04-08 04:24:21
2013-04-08 04:24:21

x2 + 12x + 36 = 0(x + 6) (x + 6) = 0

x+ 6=0 ;x + 6 = 0

x = -6 ; x = -6


001
๐ŸŽƒ
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
๐Ÿ˜‚
0
User Avatar

Related Questions


x2+12x+36=0 2x+12x+36=0 14x+36=0 14x=-36 x=-36/14 x=-2 4/7


This is not an inequality. This is an equation.12x+7=43 12x=36 x=3


x^2 + 12x = 5 x^2 + 12x + __ = 5 + __ x^2 + 12x + 36 = 5 + 36 (The 36 I got from taking half of 12 and then squaring that number (which is 6).) (x + 6)^2 = 41 x + 6 = (the square root of 41) x = (the square root of 41) - 6. Hope that helped :)


=>2x - 12x + 36 = 0 =>10x = 36=>x = 3.6Another contributor's answer:This is a quadratic equation question:x2-12x+36 = 0When factorised:(x-6)(x-6) = 0


Depending on whether or not there are implied brackets: x + 62 = x + 36 (x + 6)2 = x2 + 12x + 36


The graph is a circle with a radius of 6, centered at the origin.


6 squared is 36. 36 plus 3 is 39


36.1. You take the coefficient of x : = 122. Halve it : = 63. Then square it : = 364. Add it.This gives x2 + 12x + 36 = (x + 6)2The above method only works if the coefficient of x2 is 1. If it is not then the processs is slightly more complicated.


It is: 36 plus 121 = 157



We have 3x+9y=36, or equivalently 12x+36y=144. We also have 12x+4y=18, so subtracting these we have 32y=126 or y=63/16. Substituting this into our original equation leaves 3x=36-9*63/16 or x = 12-3*63/16 = 3/16. So: x=3/16, y=63/16


If by d2 you mean d squared then it is non linear


36. 4 squared is 16...16 + 20 - = 36.


Because 6 squared equals 36 and 36 terminates, or ends, which makes it rational.


If you're looking to solve for x, you can do so as follows: x2 + 12x - 6 = 0 x2 + 12x + 36 = 42 (x + 6)2 = 42 x + 6 = ± √42 x = -6 ± √42


x^2 + 12x + 36 = 0(x + 6)(x + 6) = 0(x + 6)^2 = 0√(x + 6)^2 = ± √0x + 6 = 0x + 6 - 6 = 0 - 6x = 6



It is a quadratic equation and its solutions are: x = 4 or x = -9


Add 9x to each side: 12x + 11 = -25Subtract 11 from each side: 12x = -36Divide each side by 12: x = -3


The expression (12x + 36)/48x can be simplified by factoring out 12/12 from the expressions. This leaves (x + 3)/4x.




If: x^2+y^2 = 12x-10y-12 Then: x^2+y^2-12x+10y = -12 Completing the squares: (x-6)^2+(y+5)^2 -36-25 = -12 So: (x-6)^2+(y+5)^2 = 49 Therefore the centre of the circle is at (6, -5) and its radius is 7


x2 - 12x + 36 = (x - 6)2


6x2-2x+36 = 5x2+10x 6x2-5x2-2x-10x+36 = 0 x2-12x+36 = 0 (x-6)(x-6) = 0 x = 6 or x = 6 It has two equal roots.



Copyright ยฉ 2020 Multiply Media, LLC. All Rights Reserved. The material on this site can not be reproduced, distributed, transmitted, cached or otherwise used, except with prior written permission of Multiply.